Extended-spectrum β-lactamases-producing Escherichia coli from a tertiary hospital in Malaysia: emergence of CTX-M-type β-lactamases variation - Sekawi, Zamberi; Yusof, Rusmah; Shamsudin, Mariana Nor (Academic Journals, 2008)
A study was conducted to portray a preliminary characteristic of extended-spectrum β-lactamases (ESBLs)-producing Escherichia coli in a local tertiary hospital in Malaysia. Sixteen clinical isolates of ESBLs producing E. coli from different sources were examined for blaSHV/TEM/CTX-M ESBL genes by PCR molecular assay. Each strain was found to carry at least one of the genes. This study demonstrated a high prevalence of blaCTX-M (81.3%) and blaTEM genes (75%). Only two strains (12.5%) carried the blaSHV gene. Nucleotide and deduced protein sequences determination showed; 61% produced CTX-M-15, 31% produced CTX-M-14 and 8% produced CTX-M-3. The antimicrobial susceptibility testing data determined that almost all sixteen isolates were resistant to oxyimino-cephalosporins, 46% resistant to gentamicin, 69% resistant to trimethoprim-sulfamethoxazole and 46% resistant to ciprofloxacin. This study preliminary emphasizes the epidemiology of the ESBL-producing E. coli particularly SHV, TEM and CTX-M-type producing E. coli in Malaysia.